Duration of Remission of Topical Psoriasis Therapies. Issue 1 (March 2013) - Levin, Ethan C.; Gupta, Rishu; Shinkai, Kanade
Topical medications are a mainstay of psoriasis therapy. Choosing a therapy with a favorable duration of remission is important in preventing disease relapse. Our aim was to review available data on the duration of remission of different topical therapies used in the treatment of psoriasis. We performed a PubMed search for English language literature that evaluated the duration of remission for topical therapy of psoriasis. Data were reviewed for Goeckerman therapy, Ingram therapy, topical corticosteroids, vitamin D derivatives, tazarotene, anthralin, and coal tar. The combination of a superpotent corticosteroid with anthralin or a vitamin D derivative induced longer remission than either of these agents as monotherapy. The longest duration of remission was reported in patients treated with Goeckerman or Ingram therapy. The mean time to relapse in 3 retrospective Goeckerman studies was 9.5 months, 1.7 years, and 2.6 years. Superpotent topical corticosteroids combined with a second agent, such as anthralin or vitamin D derivatives, may increase duration of remission compared with monotherapy. Goeckerman and Ingram therapies may provide the longest duration of remission among topical psoriasis treatments.